Factors Affecting Variation In Levels Of Participation In Watershed Management Programs In Iran - Bagherian, Reza (2009)

(untitled)
This study was designed to determine the factors that affect variation of level of participation in Watershed Management Programs (WMP) in Iran. In this regard, a conceptual model was developed to: 1) identify characteristics that lead to the participation in WMP, and 2) determine the factors that affect variation of level of participation in WMP. In this study the relationship of five factors with level of participation were examined to provide the role of each factor in explaining the variation of level of participation in WMP. These factors were; 1) socio demographic characteristics of the respondents, 2) respondents knowledge of WMP, 3) respondents attitude toward WMP, 4) respondents expectations of WMP, and 5) respondents satisfaction of prior programs as independent variables and the level of participation as dependent variable.In order to achieve to this goal, a cross sectional survey was design and utilized. The data were gathered through personal interview by using a set of questionnaire. data were collected from two hundred respondents which were randomly selected from three villages in Hable-Rud basin in Iran. Descriptive analysis, factor analysis, Pearson product moment correlation, one way analysis of variance and multiple regressions were employed for analyzing data in this study.